Analgesia and sedative effects of a fixed nitrous oxide/oxygen mixture on supragingival scaling patients: a study protocol for a randomised controlled trial - Lu Tang; Yuchen Wang; Fan Sun; Chenxi Sun; Xiaochen Jiang; Weifeng Wang; Xueling Qiu; Xiaona Sui; Lingjun Zhou (BMJ Open, 2025)
Introduction Pain during supragingival scaling is often uncomfortable for patients, causing varying degrees of fear and anxiety, thus affecting patient comfort and compliance during treatment and reducing the effectiveness of treatment. Nitrous oxide/oxygen mixtures have the advantages of analgesic and sedative effects and are well tolerated. The purpose of this study is to explore the safety and effectiveness of a fixed inhaled nitrous oxide/oxygen mixture analgesia technology in the process of supragingival scaling and to provide empirical evidence for patients to reduce pain and reduce anxiety during supragingival scaling.Methods and analysis This is a randomised, double-blind, placebo-controlled trial that is expected to enrol 120 patients. We will recruit patients undergoing supragingival scaling procedures. Participants will be allocated randomly to either the intervention group (A) or the control group (B) in a 1:1 ratio. Dental hygienists, dental assistants, patients and the collector of the data will all blind themselves to the study. Nurses who carry out the intervention will give doctors envelopes containing the patient’s identification code and the group to which they have been assigned (Group A or Group B). Group A will be given the standard treatment plus a premixed combination of nitrous oxide and oxygen, while Group B will receive oxygen alone in the standard treatment without any sedative analgesics, all under uniform conditions. Evaluations will take place prior to treatment (T0), at 5 min into the intervention (T1), at 15 min during the intervention (T2) and 5 min following the treatment (T3). The primary outcomes will be pain scores and anxiety scores, which will be assessed using the Numeric Rating Scale and the Visual Analogue Scale for Anxiety. Secondary outcome indicators in this study will include patients’ vital signs, side effects and physician and patient satisfaction.Ethics and dissemination This study was approved by the Medical Ethics Committee of the 960th Logistics Support Force of the People’s Liberation Army. Written informed consent form will be obtained from each participant. Results will be submitted for publication in peer-reviewed journals.Trial registration number ChiCTR2400090261.Protocol version Protocol version 1.1.